2010
DOI: 10.1677/erc-09-0269
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of MG132-mediated cell death by peroxiredoxin 1 through influence on ASK1 activation in human thyroid cancer cells

Abstract: Proteasome inhibitors represent a novel class of antitumor agents with pre-clinical and clinical evidence of activity against hematologic malignancies and solid tumors. However, emerging evidence indicates that antiapoptotic factors may also accumulate as a consequence of exposure to these drugs, thus it seems plausible that the activation of survival signaling cascades might compromise their antitumoral effects. Peroxiredoxins (PRDXs) are a family of thiol-containing peroxidases identified primarily by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…We have previously reported that ASK1 was involved in MG132-mediated thyroid cancer cell death. (33) Similar to in thyroid cancer cells, MG132 activated endogenous ASK1, as well as its downstream effectors p38 and JNK in U87 and SF295 glioma cells (Fig. 4A), indicating that MG132 also activated the ASK1-p38 and the ASK1-JNK pathways in glioma cells.…”
Section: Resultssupporting
confidence: 71%
“…We have previously reported that ASK1 was involved in MG132-mediated thyroid cancer cell death. (33) Similar to in thyroid cancer cells, MG132 activated endogenous ASK1, as well as its downstream effectors p38 and JNK in U87 and SF295 glioma cells (Fig. 4A), indicating that MG132 also activated the ASK1-p38 and the ASK1-JNK pathways in glioma cells.…”
Section: Resultssupporting
confidence: 71%
“…In addition, PRDX1 may exerts its tumor-promoting function by affecting intracellular signaling pathways that affect apoptosis. In thyroid cancer cells, it inhibits apoptosis through the inhibition of apoptosis signal-regulating kinase 1 (ASK1) activity (72), whereas in human hepatoma it suppresses the redox-dependent activation of caspases, inducing tumor necrosis factor-α (TNFα)-related apoptosis-inducing ligand (TRAIL) resistance (73). …”
Section: Prdxs In Tumorigenesismentioning
confidence: 99%
“…Prx1 has been implicated in both positive and negative regulation of ASK1 (34,50,170). In the context of neurodegeneration and oxidative stress, treatment of catecholaminergic PC12 cells with MPP + (Complex I inhibitor) was reported to lead to diminution of Prx1 levels, concomitant with increased apoptosis (34).…”
Section: Oxidative Stress and Apoptosismentioning
confidence: 99%